The Effect of Using Twice's Girlband K-pop as The Brand Ambassador on Increasing The Value of The Scarlett Whitening Brand - Natassja, Eileen; Simamora, Bilson (Global Research on Economy, Business, Communication, and Information, 2023)
Brand name plays a significant role in the sustainability of the business. Scarlett Whitening uses Korean public figures, namely K-Pop Twice, as the communicator to sth strengthen its image. This study aims to see whether there is an effect of using a Korean brand ambassador on increasing the brand value of Scarlett Whitening. There are four dimensions of brand ambassador used as independent variables of brand value. The data from 105 respondents that were chosen judgmentally was analyzed using multiple linear regression. The study found that visibility and credibility indicators had a positive but not significant effect on brand value, while attraction and power indicators had a positive and significant effect on brand value. So the conclusion is that the hypothesis in this study is accepted because brand ambassadors are proven to have a positive influence on brand value.